Assessment of imiloxan as a selective alpha 2B-adrenoceptor antagonist. - Michel, A. D. (1990)
1. The alpha 2-adrenoceptor binding sites of rabbit spleen and rat kidney, labelled with [3H]-rauwolscine, were characterized using a range of subtype selective ligands. 2. In rabbit spleen, the alpha-2-adrenoceptor binding sites displayed high affinity for oxymetazoline and WB 4101 and low affinity for prazosin and chlorpromazine suggesting the presence of an alpha 2A subtype. 3. There was evidence for heterogeneity of the alpha 2-adrenoceptor binding sites present in rabbit spleen. The results obtained with oxymetazoline and WB 4101 indicated that at least 75% of the [3H]-rauwolscine binding sites in this preparation displayed a pharmacology consistent with the presence of an alpha 2A subtype. 4. In rat kidney, the alpha 2-adrenoceptor binding sites displayed high affinity for prazosin and chlorpromazine and low affinity for oxymetazoline and WB 4101 suggesting the presence of an alpha 2B subtype. 5. The inclusion of guanylylimidodiphosphate (Gpp(NH)p, 0.1 mM) did not modify the pharmacology of the alpha 2-adrenoceptor binding sites present in the two preparations. Furthermore, when the two membrane preparations were combined, the resultant pharmacology was still consistent with the presence of two receptors that retained the characteristics of the alpha 2A and alpha 2B subtypes. 6. Imiloxan was identified as a selective alpha 2B ligand while benoxathian displayed a high degree of selectivity for the alpha 2A-adrenoceptor binding site. The selectivity of imiloxan for the alpha 2B-adrenoceptor binding site, coupled with its specificity for alpha 2-adrenoceptors, should make it a valuable tool in the classification of alpha 2-adrenoceptor subtypes.